The Frequency and Association of ABCA1 (C69T) Single Nucleotide Polymorphism with Type 2 Diabetes Mellitus Among Hospital Attending Patients: A Case – Control Study: ABCA1 (C69T) single nucleotide polymorphism with type 2 Diabetes mellitus - Mbasani, Rogious; Xigang, Luo; Kabuye, Deo; Misilanga, Nelson (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Type 2 diabetes mellitus (T2DM) accounts for the biggest percentage of the global diabetic burden and its onset and pathogenesis are complicated with multiple factors associated to the disease development. In this study we analyzed frequency and association of ABCA1 (C69T) single nucleotide polymorphism with type 2 Diabetes mellitus among hospital attending patients. Methods. Genotyping of ABCA1 (C69T) was performed using real time polymerase Chain Reaction in all participants. Genotypes were counted from all participants to determine genotype and allele frequency, and all possible genetic models were constructed. The genetic models and allele frequencies were used to determine the association of ABCA1 (C69T) SNP and type 2 diabetes mellitus using SPSS, 25.0 software. Results. The frequency of TT genotype was higher in T2DM patients 30 (27.3%) compared to 12 (12.0%). In controls, a significant association between TT vs. CC genetic model T vs. C allelic model with T2DM, (Odds Ratio (OR), 95% Confidence Interval (95%CI), OR: 2.596 [1.202 – 5.608], P 0.015 and OR: 1.632 [1.086 – 2.453], P 0.018 respectively with T2DM. Conclusion. The findings of our study show an association for ABCA1 (C69T) gene polymorphism with type 2, diabetes among hospital attending diabetic patients.